Analytical control of diclofenac removal in the photocatalytic oxidation process = Kontrola analityczna usuwania diklofenaku w procesie fotokatalitycznego utleniania - Bohdziewicz, Jolanta; Kudlek, Edyta; Dudziak, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Continuously increasing pharmaceuticals consumption contributes to the increase of their concentration in the aqueous environment, which is at a level of a few ng/dm3to several ?g/dm3. A numerous group of pharmaceuticals occurring in surface waters are non-steroidal painkillers and anti-inflammatory drugs, which include diclofenac.
Keywords: stężenie farmaceutyków w ściekach; usuwanie diklofenaku; fotokataliza; utlenianie; absorbancja w UV; węgiel organiczny; diclofenac; photocatalysis; absorbance in UV; organic carbon